(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
Commoner’ women in politics in the Late Middle Ages: first steps of a study Historiography has for years been valorizing the patronage and agency of aristocratic women and the relevance of women in economic, productive, commercial and religious or heretical fields. However, the commoner’ women still remain politically invisible, as the title of an early article by Diane Owen Hughes states (Invisible Madonnas?). These starting investigation, however, show that ‘communer’ women were active in politics. Indeed, they appear in chronicle, normative and judicial sources, while considering that much of their activity, including political activity, is obscured by collective names and the use of the overextended masculine, as well as by the misogynistic mentality that characterizes the society, culture and, therefore, the writing of the authors, all men. Building on the differences and similarities in the way women’s political presence is documented from one source to another, some research focuses are presented on a topic that to date has not yet been analyzed by historiography. Leaders and gregarious, manipulated and manipulative, solitary and in groups, communer’ women appear politically involved in the sources to document a participation that dates back to the early medieval centuries and lands in the Renaissance, worthy of finally being studied.